Mobility changes occasioned by COVID-19 lockdown measures: evidence from an emerging economy - Agyemang, Ernest; Agyei-Mensah, Samuel; Sivakumar, Aruna; Nathavni, Ricky; Ezzati, Majid (TeMA - Journal of Land Use, Mobility and Environment, 2025)
The unprecedented and drastic emergency responses that accompanied the declaration of COVID-19 as a pandemic have highlighted and intensified mobility injustices worldwide. Most of the global interest in the impact of COVID-19 on mobility patterns has come from developed countries, leaving a gap in literature specifically focused on Africa. This paper aims to fill that gap by examining the effects of government-imposed travel restrictions on people's attitudes and mobility behavior in urban Ghana. Using a combination of data sources, including surveys and photographic evidence, we analyze the spatial variations in mobility patterns during the lockdown. Our findings from statistical analyses and time-lapsed images indicate that many young people, informal sector workers, and individuals living in disadvantaged neighborhoods largely ignored the lockdown order. In contrast, most formal sector employees utilized internet-enabled telecommuting, e-learning opportunities, and telephone communications during the lockdown period. The paper concludes with policy recommendations aimed at enhancing mobility justice for all in the face of future public health crises and social emergencies that may require physical mobility restrictions.